2021
DOI: 10.1186/s40779-021-00342-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding neutralising antibodies against SARS-CoV-2 and their implications in clinical practice

Abstract: SARS-CoV-2 is a newly identified member of the coronavirus family that has caused the Coronavirus disease 2019 (COVID-19) pandemic. This rapidly evolving and unrelenting SARS-CoV-2 has disrupted the lives and livelihoods of millions worldwide. As of 23 August 2021, a total of 211,373,303 COVID-19 cases have been confirmed globally with a death toll of 4,424,341. A strong understanding of the infection pathway of SARS-CoV-2, and how our immune system responds to the virus is highly pertinent for guiding the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(132 citation statements)
references
References 113 publications
5
125
0
2
Order By: Relevance
“…Further, it was clear that the functionality of adaptive immunological components is more important than just sole quantity [5]. In line with this, it became evident that a diagnostic focus should be on the neutralizing the potency of detected anti-SARS-CoV-2-antibodies [6,7]. Correlations between the severity of clinical courses of COVID-19 disease and neutralizing antibody titers could be shown [8][9][10][11].…”
Section: Introductionmentioning
confidence: 88%
“…Further, it was clear that the functionality of adaptive immunological components is more important than just sole quantity [5]. In line with this, it became evident that a diagnostic focus should be on the neutralizing the potency of detected anti-SARS-CoV-2-antibodies [6,7]. Correlations between the severity of clinical courses of COVID-19 disease and neutralizing antibody titers could be shown [8][9][10][11].…”
Section: Introductionmentioning
confidence: 88%
“…Regarding natural infection, Gozalbo-Rovira et al reported weak correlations between antibody levels and inflammatory biomarkers (ferritin, D-dimer, CRP, lactate dehydrogenase (LDH), and interleukin-6) [123,124]. These correlations could be explained by the relationship between the magnitude of antibody response with the hyperactivation of the immune system in patients with severe COVID-19.…”
Section: Factors Affecting Nab Productionmentioning
confidence: 99%
“…However, we cannot rule out the possibility that Mab5-mediated neutralizing activity might be blocked through a yet unknown mechanism different from binding interference because a plurality of options allow SARS-CoV-2 entry during infection (43,44), such as the sequential endocytosis of SARS-CoV-2 infection observed in Vero E6 cells (45). The viral-antibody complex may prevent infections by interfering with virus binding to receptors, blocking uptake into cells, preventing uncoating of the genomes in endosomes, or causing virion aggregation (46). Most importantly, we determined that Mab5 indeed played a protective role in mitigating viral infection in live animal experiments (Figure 3-5), which makes our identified antibody a promising compound for therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%